PROFIL PENGUASAAN MATERI MATEMATIKA SEKOLAH MAHASISWA PENDIDIKAN MATEMATIKA SEMESTER VI - Marfi Ario (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Each teacher is required to have pedagogic, personality, professional, and social competence. Professional competence refers to the ability of mastery of learning materials widely and deeply that enables to guide learners meet the established competency standards. Based on this, every mathematics teacher candidate must have good mastery of school mathematic materials. This study aims to determine the profile of mastery of school mathematics materials students of mathematics education program semester VI. It is important to know the readiness of students to become professional math teachers. This research is a descriptive research. The study sample consisted of 2 classes with 48 students. Data collected through the test. The test results were analyzed using descriptive statistics. The results showed that the mastery of mathematics materials of students school semester VI is very low at 22.5%. This indicates that students as math teacher candidates do not have professional competence. The results of this study is expected to be a source of information for stakeholders to develop learning and curriculum that are able to prepare students who are competent in mastery of school mathematics materials